2012
DOI: 10.1177/1468087412450987
|View full text |Cite
|
Sign up to set email alerts
|

The effects of split injections on high exhaust gas recirculation low-temperature diesel engine combustion

Abstract: Diesel engine emissions of oxides of nitrogen and smoke can be reduced simultaneously through the use of high levels of exhaust gas recirculation to achieve low-temperature combustion. However, single fuel injection per cycle diesel low-temperature combustion is also characterized by high fuel consumption and high total unburned hydrocarbons and carbon monoxide emissions. This work focuses on investigating the potential of a split (50/50) main fuel-injection strategy to reduce smoke, total unburned hydrocarbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…It has been predicted 13 that near-zero NO x and soot levels could be achieved in a premixed charge compression ignition (PCCI) engine with an optimized low-pressure early-cycle fuel injection combined with a high-pressure near-TDC injection strategy; this split-injection strategy allowed good control over the combustion phasing. In previous work by the present authors, 15 a split-fuelinjection (50:50 by mass) strategy was shown to reduce the EGR requirements from 62 vol % (about 8% intake oxygen mass fraction) to 52 vol % (about 12% intake oxygen mass fraction) to achieve near-zero NO x and smoke emissions at 120 kPa intake pressure. The THC and CO emissions were reduced significantly with improved fuel efficiency at 12% intake oxygen mass fraction with the split-injection strategy compared with the single-injection strategy at 8% intake oxygen mass fraction.…”
Section: Introductionmentioning
confidence: 71%
“…It has been predicted 13 that near-zero NO x and soot levels could be achieved in a premixed charge compression ignition (PCCI) engine with an optimized low-pressure early-cycle fuel injection combined with a high-pressure near-TDC injection strategy; this split-injection strategy allowed good control over the combustion phasing. In previous work by the present authors, 15 a split-fuelinjection (50:50 by mass) strategy was shown to reduce the EGR requirements from 62 vol % (about 8% intake oxygen mass fraction) to 52 vol % (about 12% intake oxygen mass fraction) to achieve near-zero NO x and smoke emissions at 120 kPa intake pressure. The THC and CO emissions were reduced significantly with improved fuel efficiency at 12% intake oxygen mass fraction with the split-injection strategy compared with the single-injection strategy at 8% intake oxygen mass fraction.…”
Section: Introductionmentioning
confidence: 71%
“…As a consequence of the reduced flame temperature and lower in-cylinder oxygen concentrations found in LTC, it is usual for the emissions of unburned total hydrocarbons (THC) and carbon monoxide (CO) emissions to increase significantly. This effect has been demonstrated for a wide range of different LTC strategies including homogeneous charge compression ignition LTC [4,5], moderate EGR split injection LTC [6,7], single injection high-EGR LTC/partially premixed compression ignition LTC [8,9,10,11,12], premixed charge compression ignition LTC [13,14] and reactivity controlled compression ignition LTC [15,16]. Less homogeneous charge distribution, including locally fuel-lean and fuel-rich regimes, leads to a more stratified combustion process in high-EGR LTC compared to homogeneous charge approaches.…”
Section: Introductionmentioning
confidence: 88%
“…The research engine facility, which has been fully described and illustrated schematically in a number of previous works from the authors' research group, [7][8][9][10][11] was instrumented with the provision to measure boosted intake air temperature and pressure, fuel and air flow rates, and in-cylinder pressure. Intake pressure was measured using Kistler 4045A5 piezo-resistive pressure transducer while the in-cylinder pressure was measured with a piezoelectric AVL QC34C flushmounted water-cooled transducer.…”
Section: Experimental Set-upmentioning
confidence: 99%